Strategi Pengembangan Sertifikasi Kompetensi Tenaga Kerja Konstruksi Di Provinsi Sumatera Selatan Berbasis Kebutuhan dan Analisis SWOT - Oktarina Mangindaan, Vanny; Fitriani, Heni; Zainal Arifin, Doedoeng (Jurnal Manajemen Teknologi & Teknik Sipil, 2025)
Construction workforce certification is a critical issue in Indonesia's infrastructure development sector, as mandated by the Construction Services Law requiring all construction workers to obtain Work Competency Certificates (SKK). This study aims to formulate strategies for developing construction workforce construction workers in South Sumatra Province through the integration of demand analysis and SWOT analysis. A quantitative approach was applied, where secondary data were used to project certification needs for 105 construction projects planned under the 2025-2029 State Budget. In addition, primary data were collected through questionnaires and interviews identify key factors influencing SKK acquisition, which were then incorporated into the SWOT framework for strategic. Results revealed that while expert-level certification (Levels 7-9) needs are met with 1,792 certified professionals available, significant shortages exist at the technician/analyst level (Levels 4-6) with a gap of 2,139 positions and at the operator level (Levels 1-3) with a substantial deficit of 48,882 certified workers. Factor analysis identified self-motivation, wage increase prospects, time constraints, regulatory sanctions, and enhanced employment opportunities as key determinants in SKK acquisition decisions. The SWOT analysis concluded that a Strength-Opportunity (SO) strategy would be most effective, leveraging regulatory frameworks, digital certification processes, educational institution collaborations, and on-site certification to address the certification gaps. This research provides evidence-based recommendations for policymakers to develop targeted interventions that can strengthen construction workforce capacity and ensure compliance with national standards.